Overview of Stress Levels Factors in Students During Online Learning During The Covid-19 Pandemic in 2021 - Lia Ambarwati; Festia Dwi Cahyani; Fitri Rahmaningsih; Hilda Nurul Fadillah; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The government orders all learning activities to be carried out at home (learning from home) and working from home (Work From Home/WFH). because online learning has been going on for more than a year in Indonesia, therefore, this study aims to analyze the factors that affect the level of stress in students during online learning during the 2021 Covid-19 pandemic. This study aims to analyze the factors that influence the stress level of students during online learning. This research was conducted for 1 month, namely June 2021. This study uses a qualitative method with a phenomenological approach. Data collection comes from in-depth interviews with 6th-semester students and a sample of 4 students is taken. During online or online learning that students do during the Covid-19 pandemic, it affects the stress level of 6th-semester students who will soon graduate. Factors that affect the level of stress in students include internal stressors, external stressors, and stress symptom factors (psychological symptoms, physical symptoms, and behavioral symptoms). The factors that affect the level of stress in students during online learning during the Covid-19 pandemic are internal stressors, external stressors, and stress symptom factors.